A30: Assessment of Construct and Discriminative Validity of the 3‐Variable JADAS in Relation of Parent‐Reported Outcomes. Issue 11 (March 2014) - Consolaro, Alessandro; Negro, Giorgia; Gallo, Maria C.; Verazza, Sara; Calandra, Serena; Robbiano, Cristina; Ruperto, Nicolino; Martini, Alberto; Ravelli, Angelo
Abstract : Background/Purpose: An established approach to the measurement of disease activity in juvenile idiopathic arthritis (JIA) is based on the Juvenile Arthritis Disease Activity Score (JADAS). The feasibility of the JADAS for use in standard clinical practice might be enhanced by implementing of a 3‐variable version, which does not include the acute phase reactant. Recently, the 3‐variable JADAS was found to correlate closely with the original tool. However, the validity of this simplified version of the JADAS in the clinical setting is still insufficiently documented. Aim of the study was to further validate the 3‐variable version of the JADAS, hence named clinical JADAS (cJADAS), by assessing its relationship with parent‐reported outcomes (excluding the parent's rating of overall well‐being, which is included in the JADAS). Methods: The study was conducted in a cohort of 175 newly‐diagnosed consecutive JIA patients, first seen between 2007–2011 and then followed for 2 years. Clinical assessments were made at baseline and then at 6, 12, 18 and 24 months. At each visit, all parent reported outcomes included in the Juvenile Arthritis Multidimensional Assessment Report (JAMAR) were assessed by a parent of each patient. Construct validity of the cJADAS was computed by calculating its Spearman's correlation with pain visual analog scale (VAS) and disease activity VAS. Discriminative validity was evaluated, by means of the non‐parametric analysis of variance (Kruskal‐Wallis test) or Mann‐Whitney U test, by examining the ability of cJADAS to discriminate between: 1) different categories of disease state (remission, persistent activity or flare), rated subjectively by the parents; 2) different categories of disease course (improved, stable or worsened), rated subjectively by the parents; 3) visit in which parents declared themselves as satisfied or not satisfied with the outcome of the illness; 4) different duration of morning stiffness. Results: The cJADAS was strongly correlated with pain VAS (r=0.71) and disease activity VAS (r=0.77). The cJADAS was significantly lower in patients rated as being in remission than in patients rated as being in persistent activity or flare (p < 0.0001), in patients rated as improved or stable than in patients rated as worsened (p < 0001), and in patients whose parents were satisfied with illness outcome than in those who were not (p < 0.0001). The cJADAS was proportionally greater in parallel with the progressive increase in morning stiffness (p < 0001). Conclusion: The cJADAS was strongly associated with all parent‐reported outcomes, which indicates that it reflects well the parent perception of the child's disease status and course.